PENGARUH PAJAK TANGGUHAN, PERENCANAAN PAJAK DAN ASSET PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Puspitasari, Dhea Pranatania; Murdiati, Sri (PERMANA, 2018)
Objectives to be achieved in this research are: 1). To know the effect of tax deferred, tax planning and corporate assets together to earnings management at chemical company, 2). To determine the effect of deferred tax on earnings management at chemical companies, 3). To know the effect of tax planning on earnings management at chemical company, 4). To know the influence of company's asset to earnings management at chemical company. Data collection method used in this research is dentasiasi. While the data analysis and hypothesis test used are classical assumption testing, multiple linear regression analysis, simultaneous significance test (F statistic test), significant test of individual parameter (t test statistic), and Coefficient of Determination. Based on the calculation result there is significant influence of tax deferred, tax planning and company asset collectively to earnings management at chemical company proven from result of test of significant test of simultan parameter (statistic test F) got probability sig value equal to 0,022 <0,05. There is no significant partial tax effect on profit management in chemical companies as evidenced by the result of testing  the  significance  of  individual  parameters  (statistical  test  t)  of  deferred  tax  on  earnings management obtained probability sig value of 0.904> 0.05. There is significant influence of tax planning partially to earnings management at chemical company proven from result of test of significant test of individual parameter (statistic test t) tax planning to earnings management got probability sig value equal  to  0,013  <0,05.  There  is  no  significant  influence  of  company  asset  partially  to  earnings management at chemical company proved from result of calculation of test of significant individual parameter (statistic test t) company asset to earnings management got probability sig value equal to 0,166 <0,05.Keywords: Deferred Tax, Tax Planning, Company Assets, Profit Management